Prophylactic actions related to adverse events in elderly people hospitalized in Intensive Care Units: reflections on the health education process (Research, Society and Development, 2022)
The relevance of the study is applied due to the importance of debating this theme, and thus enabling a critical reflection on the methods of health education. The objective was to reflect on the prophylactic measures related to adverse events in Intensive Care Units in elderly patients, relating to the importance of the health education process. This is a narrative review of the literature, with a qualitative aspect. The data search took place in the following databases: Database on Nursing (BDENF), Latin American and Caribbean Literature on Health Sciences (LILACS), Medline, and Scientific Electronic Library Online (SciELO), identified through the Virtual Library. in Health (BVS) and PubMed. The research took place from November 2021 to January 15, 2022, and the descriptors “Elderly”, “Prevention”, “Adverse Events”, “Intensive Care Unit” and “Health education” established in the list were used. Health Science Descriptors (DECs). It was found that the occurrence of adverse events is directly linked to failures in care and lack of knowledge to carry out specific prophylactic practices for each complication, the main ones being related to medications, infections and wounds. It is concluded that the production of reflections on this theme is essential to awaken in professionals and the community the importance of debating issues related to health education, and thus improve the care offered to the elderly in intensive care.